2019
DOI: 10.3897/rrpharmacology.5.38769
|View full text |Cite
|
Sign up to set email alerts
|

Selank and semax as potential hepatoprotectors in medical treatment of tuberculosis

Abstract: Introduction: Drug-induced hepatitis is common in clinical practice. This problem is particularly relevant in the treatment of tuberculous infection, because for this purpose, up to 5–6 hepatotoxic drugs are used simultaneously for a long time, which often (in 15–20% of cases) leads to medical liver lesion. To protect the liver, Semax and Selank are offered – drugs of regulatory peptides group. Materials and Methods: The research was conducted on 96 outbred white male rats weighing 180–220 g. The exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…6 More and more attention is being paid to the development of short-chain peptide drugs for the cytoprotection. [7][8][9][10][11] in particular, neuroprotection. 12,13 The heptapeptide semax (Met-Glu-His-Phe-Pro-Gly-Pro) is a synthetic analogue of ACTH (4)(5)(6)(7)(8)(9)(10) which exerts marked nootropic and neuroprotective activities, 14 protects effectively brain against ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 More and more attention is being paid to the development of short-chain peptide drugs for the cytoprotection. [7][8][9][10][11] in particular, neuroprotection. 12,13 The heptapeptide semax (Met-Glu-His-Phe-Pro-Gly-Pro) is a synthetic analogue of ACTH (4)(5)(6)(7)(8)(9)(10) which exerts marked nootropic and neuroprotective activities, 14 protects effectively brain against ischemic stroke.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11] in particular, neuroprotection. 12,13 The heptapeptide semax (Met-Glu-His-Phe-Pro-Gly-Pro) is a synthetic analogue of ACTH (4)(5)(6)(7)(8)(9)(10) which exerts marked nootropic and neuroprotective activities, 14 protects effectively brain against ischemic stroke. 13 Studies have shown that semax promotes the survival of neurons during glutamate excitotoxicity, 15 protects against atrophy of the optic nerve and optic neuritis of inflammatory or toxic-allergic etiology.…”
Section: Introductionmentioning
confidence: 99%
“…Special interest is paid to the development of short-chain peptide drugs for the cytoprotection [8,9,10,11,12], in particular, neuroprotection [13,14]. One of the actively studied classes of peptide regulators are melanocortins, which accelerate regeneration in the neuromuscular system, have a protective effect on damage to the central nervous system.…”
mentioning
confidence: 99%